1997
DOI: 10.1016/s0735-1097(97)00116-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytokine Expression in Leukocytes in Acute Myocardial Infarction

Abstract: Plasma from the ischemic and reperfused heart stimulates the expression of IL-1 beta and IL-8 in leukocytes. Therefore, leukocyte-derived cytokines may contribute to the regulation of cardiac inflammatory responses in patients with an acute MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 31 publications
1
58
1
Order By: Relevance
“…Interleukin-6 seemed to be an important cytokine produced by the injured myocytes in a study of 15 patients with AMI (11), and strong negative correlation between serum IL-6 concentration and left ventricular ejection fraction (LVEF) has been demonstrated (12). Similar observations have been made by studying tumor necrosis factor-a (TNF-a), IL-1a and soluble IL-2 receptor (sIL-2-R) which were found to be significantly elevated in AMI, with the highest levels noted in the most severe and complicated cases of myocardial infarction (9,13).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interleukin-6 seemed to be an important cytokine produced by the injured myocytes in a study of 15 patients with AMI (11), and strong negative correlation between serum IL-6 concentration and left ventricular ejection fraction (LVEF) has been demonstrated (12). Similar observations have been made by studying tumor necrosis factor-a (TNF-a), IL-1a and soluble IL-2 receptor (sIL-2-R) which were found to be significantly elevated in AMI, with the highest levels noted in the most severe and complicated cases of myocardial infarction (9,13).…”
Section: Introductionmentioning
confidence: 71%
“…On the other hand, the association between serum levels of cytokines and myocardial ischemia and injury is under investigation. It is known from several studies that several cytokines can be found elevated in patients with cardiac ischemia or AMI (7)(8)(9). From in vitro studies it is of particular interest that ischemic myocytes produce cytokines such as interleukin-6 (IL-6) and its synthesis is accelerated by reperfusion (10).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the previous results showing depletion of circulating leukocytes and loss of IL-8 immunoreactivity in postischemic myocardial tissue. 54 It is well known that IL-8 is a potent chemoattractant and activator of neutrophils. 55,56 Therefore, IL-8 produced by neutrophils infiltrating the infarcted myocardium might be responsible for subsequent accumulation and activation of neutrophils, leading to an increase in myocardial cell damage due to the neutrophil-mediated microvascular obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA of 10 7 ECV-304 cells or 2.5ϫ10 7 mononuclear cells was isolated with the RNeasy Mini Kit (Qiagen GmbH) and analyzed by Northern blotting as described previously. 25 Briefly, 5 g of total RNA of each sample was subjected to electrophoresis on a 1.2% agarose gel containing 100 mmol/L MOPS (Boehringer), 40 mmol/L sodium acetate (Boehringer), 5 mmol/L EDTA, and 6% formaldehyde (Boehringer). The RNA was transferred to nylon membrane (Hybond-N, Amersham) in 20ϫ SSC (Merck) by capillary blotting overnight.…”
Section: Rna Preparation Northern Blot Analysis and Electrophoreticmentioning
confidence: 99%